Contribution of the Aceh High Prosecutor's Office Library in Handling Legal Cases (Analysis of Legal Collection Utilization) - Rizqiya Safira; Abdul Manan; Khatib A. Latief; Mukhtaruddin Mukhtaruddin; T Mulkan Safri (AL Maktabah, 2025)
Abstract:The library serves as an information center that supports the effectiveness of institutional performance, including law enforcement agencies such as the Prosecutor's Office. The handling of legal cases requires accurate and relevant information to support decision-making, expedite case resolution, and ensure justice. This study aims to examine the contribution of the Aceh High Prosecutor’s Office Library in handling legal cases by analyzing the utilization of its legal collections. The research employs a qualitative approach, with data collected through interviews, observation, and document analysis. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the library makes a tangible contribution by providing legal collections that are used to support the drafting of indictments, case analysis, and court proceedings. However, the utilization of these collections is not yet optimal due to several obstacles, such as delayed book returns and low awareness among some staff members regarding the strategic role of the library. Therefore, strategies are needed to enhance the use of the collections through regular updates and improved information literacy among employees, so the library can be fully utilized to support professional performance.